Peningkatan Kemampuan Kognitif Anak Melalui Media Lingkungan Pada Anak Usia 5-6 Tahun di TK Kristen Melati Makariki Kecamatan Amahei Kabupaten Maluku Tengah - Desyane Erlins Karolis; H. Abarua (Peneliti.net, 2022)
The purpose of this study was to describe the cognitive improvement of children through environmental media at Tk Kristen Melati Makariki, Amahei District, Central Maluku Regency. This research uses the type of Classroom Action Research (CAR). Based on the results of research conducted at the Melati Makariki Christian Kindergarten, there were 29 children, using environmental media, it turned out that there was an increase in the mastery of using environmental media in improving children's thinking skills. In class learning activities with the knowledge that children have to distinguish stones through environmental media and can count well or clearly.